2009
DOI: 10.1042/bsr20080023
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified adenoviral vector with the protein transduction domain of Tat improves gene transfer to CAR-deficient cells

Abstract: The transduction efficiency of Ad (adenovirus) depends, to some extent, on the expression level of CAR (coxsackievirus and Ad receptor) of a target cell. The low level of CAR on the cell surface is a potential barrier to efficient gene transfer. To overcome this problem, PTD.AdeGFP (where eGFP is enhanced green fluorescent protein) was constructed by modifying the HI loop of Ad5 (Ad type 5) fibre with the Tat (trans-activating) PTD (protein transduction domain) derived from HIV. The present study showed that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Electron microscopy study on the obtained fiber modified adenoviruses demonstrated typical dispersedly distributed adenoviral particles except for Ad5HI-Tat PTD virus. The particles of the latter formed aggregates (data not shown), which was consistent with our previous study (Liu et al, 2009).…”
Section: Transduction Of Knob Modified Adenovirus In Target Cells In supporting
confidence: 93%
See 1 more Smart Citation
“…Electron microscopy study on the obtained fiber modified adenoviruses demonstrated typical dispersedly distributed adenoviral particles except for Ad5HI-Tat PTD virus. The particles of the latter formed aggregates (data not shown), which was consistent with our previous study (Liu et al, 2009).…”
Section: Transduction Of Knob Modified Adenovirus In Target Cells In supporting
confidence: 93%
“…Synthetic small peptide RGD, Tat PTD, NGR or poly-lysine (pK7) has been used to modify the fiber knob genetically by other groups to improve the tropsim of adenovirus (Bouri et al, 1999;Wickham et al, 1997;Dmitriev et al, 1998;Han et al, 2007;Liu et al, 2009;Mizuguchi et al, 2005;Zheng et al, 2007). In addition, a peptide SIK-VAV was recently showed to be able to bind to alpha integrin and chemically modified adenoviral vector using SIKVAV peptide could increase gene transfer to alpha integrin positive cells (Stevenson et al, 2007).…”
Section: Generation Of Fiber-modified Adenoviral Vectors Using Prgfmamentioning
confidence: 96%
“…A number of strategies have been developed, primarily based on the use of bispecific antibodies (25,26), creation of fiber-chimeric Ad (13)(14)(15)(16) and direct incorporation into viral capsid of peptide analogues specific for a tumor-associated receptor (17)(18)(19)(20)(21). The latter has been preferred for cancer cellspecific Ad retargeting, in which finding new cancer targeting peptides is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviruses, such as HIV and murine leukemia virus (MLV), have their protein capsid enclosed in a lipid envelope while adenovirus and adeno-associated virus are non-enveloped viruses with only a protein capsid and envelope protein on their surface. In both cases, the outer layer of the virus has a negative surface charge at physiological pH [119] and is responsible for initiating infection. Proteins responsible for the binding of the virus with the cell membrane are located on the virus capsid or embedded in the lipid envelope of the virus.…”
Section: Current Applications Using the Noncovalent Strategymentioning
confidence: 99%